Identification of Bacteria in Foot Wound Swabs from Patients Diabetes Mellitus - Nurul Humairoh; Ni Nyoman Ariwidiani; Baiq Isti Hijriani (Poltekkes Kemenkes Kupang, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia that predisposes patients to impaired wound healing and chronic infections, including diabetic foot ulcers. Bacterial colonization of these wounds plays a critical role in delayed healing, increased morbidity, and risk of amputation. This study aimed to identify the bacterial profiles isolated from foot wound swabs of patients with diabetes mellitus. A descriptive observational study was conducted using foot wound swab samples collected from patients with diabetes mellitus receiving wound care at Mandalika Care, Mataram City. Bacterial identification was performed through macroscopic and microscopic examination, Gram staining, and standard biochemical tests following culture on Blood Agar Plate (BAP) and MacConkey Agar (MCA). Data were analyzed descriptively and presented as frequencies and percentages. Six samples met the inclusion criteria and were analyzed. All isolates were Gram-negative bacteria. The bacterial species identified were Pseudomonas aeruginosa (33,36%), Morganella morganii (16,6%), Pseudomonas putrefaciens (16,6%), Enterobacter agglomerans (16,6%), and Pseudomonas mallei (16,6%). The conclusion is that Gram-negative bacteria predominated in diabetic foot wound infections in this study, with Pseudomonas aeruginosa being the most frequently isolated species. These findings highlight the importance of early microbiological examination to guide appropriate wound management and antimicrobial therapy in diabetic patients.